2019
DOI: 10.1002/ptr.6590
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of natural, peroxide‐free tooth‐bleaching agents: A systematic review, meta‐analysis, and technological prospecting

Abstract: The aim of this study is to analyze the efficacy of natural bleaching agents and the current technological development in this research field. Two reviewers performed a literature search up to July 2019 in 15 databases. Five laboratory studies and 25 patents were included. Data regarding natural bleaching agent used, application protocol, and the main findings of studies were analyzed. Laboratory studies that evaluated natural bleaching agents' peroxide-free or associated to peroxides and patents related to na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
8
0
2
Order By: Relevance
“…Thus, we hypothesized that the development of new whitening agents based on natural products could provide similar aesthetic results and minor side effects 12 . Up to now, it seems that despite some papers relate the use of natural compounds as dental bleaching agents, these were not more effective than the traditional techniques 14 .…”
mentioning
confidence: 99%
“…Thus, we hypothesized that the development of new whitening agents based on natural products could provide similar aesthetic results and minor side effects 12 . Up to now, it seems that despite some papers relate the use of natural compounds as dental bleaching agents, these were not more effective than the traditional techniques 14 .…”
mentioning
confidence: 99%
“…Cerca de um terço dos métodos de clareamento foi realizado sem supervisão de um cirurgião-dentista e foi apresentada também uma variedade de métodos de clareamento sem o uso de peróxidos. A literatura atual não suporta o uso de agentes caseiros ou naturais como clareamento dental 22 , ou alegações para o uso de dentifrícios à base de carvão vegetal, não havendo, assim, relatos de sua eficácia e segurança 23 . O mecanismo dos agentes naturais e das pastas clareadoras dá-se através de abrasivos e, observe-se, dentifrícios à base de carvão aumentam a rugosidade da superfície dental, com valores estatisticamente significativos após um mês de escovação usando creme dental contendo carvão 24 .…”
Section: Discussionunclassified
“…Some vegetablederived enzymes, such as papain and bromelain, have been tested in dentifrices, with an intention to help with the degradation of the acquired pellicle (34) and improve stain removal (99). A recent systematic review with a metanalysis evaluated several natural extracts, chlorine dioxide, sodium chloride, sodium bicarbonate, vinegar, etc., and their combination with peroxides, and concluded that, although they could be an alternative to tooth whitening, evidence is still scarce (29). Even so, the authors pointed out that there are a great number of patients with these products, indicating an interest of the industry in studying them and possibly developing new OTC options in the near future (29).…”
Section: Future Perspectives and General Findingsmentioning
confidence: 99%